The Spirit of the New Testament - Thomas, John Christopher (Deo Publishing, Religion and Theology Special E-Book Collection, 1999-2017, ISBN: 9789004401549., 2005)
The essays in this volume on the one hand together form an exploration of the Spirit in the New Testament, and on the other hand a demonstration of the spirit of the NT. The focus is largely on the Johannine literature, but there are also exegetical studies in Matthew and Luke. The studies are either entirely new or have already been influential among Pentecostal theologians; this publication makes them deservedly and conveniently available to a wider readership. Essays include: The Kingdom of God in Matthew; Discipleship in Mark; The Ending of Mark; The Composition of the Fourth Gospel; The Fourth Gospel and Rabbinic Judaism; The Spirit in the Fourth Gospel; Healing in the Atonement; The Structure of Acts; Footwashing; Women, Pentecostals, and the Bible; The Literary Structure of 1 John; Pentecostal Theology in the 21st Century.